Reseña - Castro-Herrera, Fabio Saúl (2014)
Gómez Serrudo, Nelson Antonio y Jefferson Jaramillo Marín. Salsa y cultura popular de Bogotá. Bogotá: Pontificia Universidad Javeriana y Fundación Universidad Autónoma de Colombia, 2013. 241pp